Purifikasi Protein Fusi MBP-Mga Streptococcus pyogenes Hasil Ekspresi Heterolog di Escherichia coli - Muhaimin Muhaimin; Oei Ban Liang; Enny Ratnaningsih; Endang Purwantini; Debbie Sofie Retnoningrum (Institut Teknologi Bandung, 2005)
Optimization of purification process of Streptococcus pyogenesâs MBP-Mga fusion protein from Escherichia coli pMALMga carrying mga49 gene had been carried out. The purification was conducted by using affinity chromatography column with amylose ligands. SDS-PAGE analysis gave a band at 104 kDa showing a pure MBP-Mga fusion protein.